MATR3 mutation analysis in a Chinese cohort with sporadic amyotrophic lateral sclerosis - Xu, Lianping; Li, Jiao; Tang, Lu; Zhang, Nan; Fan, Dongsheng (Neurobiology of aging, 2016)
Several recent studies have reported that the MATR3 gene is associated with the risk of amyotrophic lateral sclerosis (ALS). We sequenced the MATR3 gene in 509 unrelated Chinese sporadic ALS patients and 560 control subjects. We identified a novel missense mutation p.Ser610Phe in one patient. We also detected 3 missense variants (p.Ala313Gly, p.Arg147Lys, and p.Gln347Lys) in 3 of the 560 healthy controls. Our results suggest that MATR3 may not be a common genetic factor in Chinese ALS patients.